Legal Positivism, Positive Law, and the Positivisation of Islamic Law In Indonesia - Muslihun Muslihun (Universitas Islam Negeri Mataram, 2018)
This study elucidates the legal positivism and critically compares it with other schools of philosophy of law. Debates on the legislation of Islamic law in Indonesian can be traced back to the discursive practice of legal philosophy such as legal positivism. Indonesia as a law-based state (rechtsaat) adopts to a considerable degree legal positivism. However, it cannot be said that pure legal positivism, as it is promoted by its thinkers such as John Austin and Hans Kelsen, is applied because the Indonesian legal system accept morality such as religious and customary norms as the ground of legislation. By examining the postivisation of Islamic law, that is the legislation of Islamic law into the state legal system, this study argues that morale, ethics or norms derived from religion and customs are accepted to the state law. They can be used as the source of justice while justice in the positivists’ view refers to the code and statute endorsed by those who are in authority or power to do that. It thus denies the view of legal positivists who reject ethics or norms beyond the state law as non-law.